Cytotoxic and Immunomodulatory Potential Activity of Fruit Extracts on Cervical Cancer (HeLa) and Fibroblast (L929) Cells - Helen Mier-Giraldo MSc; Luis Eduardo Díaz-Barrera MSc, PhD; Lucy Gabriela Delgado-Murcia PhD; Manuel Fernando Valero-Valdivieso PhD; Gabriela Cáez-Ramírez MSc, PhDc (SAGE Publishing, 2017)
It was purposed to evaluate the biological potential of ethanol and isopropanol crude extracts of ripe Physalis peruviana fruits. Cytotoxic and immunomodulatory effects of the expression of interleukin-6, interleukin-8, and monocyte chemoattractant protein-1 (MCP-1) were evaluated on human cervical cancer (HeLa) and murine fibroblast (L929) cells. The composition was evaluated by high-performance liquid chromatography diode-array detection and high-performance liquid chromatography ultraviolet/visible detection. The presence of ursolic acid and rosmarinic acid was found in both solvents. However, gallic acid, quercetin, and epicatechin were higher in isopropanol extracts ( P < .05). The results indicated a relationship among the total polyphenol content, antioxidant activity, and cytotoxic activity that was dependent on the solvent used. Isopropanol extracts presented a half-maximal inhibition concentration value (IC 50 ) of 60.48 ± 3.8 μg/mL for HeLa cells and 66.62 ± 2.67 μg/mL for L929 fibroblasts. The extracts reduced the release of interleukin-6, interleukin-8, and MCP-1 in a dose-dependent manner. Extracts showed anticancer and immunomodulatory potential for new complementary pharmaceutical products development.